Housing policies by young people, not for young people. Experiences from a co-creation project in Amsterdam - Hoekstra, Joris; Gentili, Martina (Frontiers in Sustainable Cities, 2023)
For young adults on the Amsterdam housing market the accessibility of housing has been decreasing for years, due to soaring house prices and rents, the shrinkage and residualization of the social rental sector, and the precarization of the labor market. Consequently, many young people struggle to secure an affordable and adequate dwelling and are stuck in insecure and chaotic housing pathways. Current housing policies in Amsterdam are struggling to effectively respond to these challenges. In an effort to better understand and address the specific housing problems of young people, the Municipality of Amsterdam, housing association Lieven de Key, resident organization !Woon, Delft University of Technology and a group of local young people have started a co-creation process within the framework of the H2020 UPLIFT project. The goal of this co-creation process is to unravel the real-life experiences of young people and to co-create new or improved policy initiatives with them. This paper examines the results of said policy co-creation process in order to evaluate its methodology as well as its impact on the participating actors - young people in particular - and on the policymaking approach. We analyze the benefits and limits of this type of participatory practice in addressing housing issues and try to draw conclusions on its applicability in a larger context.